Increasing Community Capacity through the Disaster Resilient Village Program (Keltana) in Biawu Village, Gorontalo City - Tety Thalib; Ellys Rachman; Rukiah Nggilu (PT FORMOSA CENDEKIA GLOBAL, 2023)
In developing disaster resilient villages/sub-districts, stakeholders must conduct studies regarding disaster risks in their villages/sub-districts. The aim of this research is to analyze increasing community capacity through the disaster resilient subdistrict program (Keltana). The methods used are observation, discussion, socialization and evaluation methods. It is hoped that the results of the community service that has been carried out will provide a more specific understanding regarding the Disaster Resilient Village program and increase the community's capacity to remain active in protecting the environment, responding to factors that cause disasters or adopting disaster preparedness, disaster mitigation, disaster triage, basic life support. (BHD), evacuation or handling of refugees and disaster victims. This activity specifically explains how to overcome flood disasters by strengthening community capacity so that it runs effectively and efficiently.